Atopic dermatitis: a review of topical nonsteroid therapy - Papier, Ariana (Drugs Context, 2018)
BACKGROUND: Atopic dermatitis is a chronic inflammatory skin condition that affects up to 20% of children and 3% of adults globally. Although topical corticosteroids are considered to be the first-line agents, they can be associated with cutaneous and systemic adverse effects. Since the early 2000s, two new classes of nonsteroid topical therapies, topical calcineurin inhibitors and phosphodiesterase 4 (PDE4) inhibitors, have been introduced and provide a safe treatment alternative. METHOD: We performed a search and review of clinical trials that examined the safety and efficacy of topical calcineurin inhibitors and PDE4 inhibitors. The search was conducted using the PubMed database as well as preselected keywords and filters. This review focuses on the safety and efficacy of each therapy. RESULTS: Sixty-nine clinical trials identified in this study have demonstrated the efficacy and safety of topical calcineurin and a single novel PDE4 inhibitor in the treatment of atopic dermatitis. Topical calcineurin inhibitors have been shown to be effective in both achieving lesion clearance as well as reducing relapse when used long-term and proactively. Similarly, in clinical trials the PDE4 inhibitor showed success in lesion clearance and symptom management. All three therapies (pimecrolimus, tacrolimus, crisaborole) are associated with low systemic absorption. No clinical trials to date have shown an increased risk of systemic adverse events or malignancy such as lymphoma. The most commonly reported treatment-related adverse event across all three therapies was application-site discomfort, pain or pruritus. It is important to note that long-term studies are not yet available for the novel PDE4 inhibitor. DISCUSSION: Topical calcineurin inhibitors provide a safe and effective alternative to topical corticosteroid use in the treatment of atopic dermatitis. Although the US Food and Drug Administration (FDA) black box warning for topical calcineurin inhibitors remains, studies have not shown an increased risk of malignancy. These warnings have caused a decline in use in favor of topical steroids. A novel PDE4 inhibitor has shown efficacy and safety in studies up to one year. Further long-term safety data is needed.